Pengaruh Ukuran Perusahaan, Net Profit Margin Dan Return On Investment Terhadap Harga Saham Pada PT Kalbe Farma Tbk Periode 2015-2024 - Rae Nirmala; Amthy Suraya (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - This study aims to determine the effect of Company Size, Net Profit Margin (NPM), and Return on Investment (ROI) on Stock Prices at PT Kalbe Farma Tbk for the period 2015–2024, both partially and simultaneously. The research method used is a quantitative method with a descriptive approach. The data used are secondary data obtained from the annual financial reports of PT Kalbe Farma Tbk published through the Indonesia Stock Exchange (IDX). Data analysis techniques used include descriptive statistical analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation tests), multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination (R²) tests. The results of the study indicate that partially, Company Size, Net Profit Margin (NPM), and Return on Investment (ROI) do not significantly influence the stock price of PT Kalbe Farma Tbk. Simultaneously, Company Size, Net Profit Margin (NPM), and Return on Investment (ROI) also have no significant effect on stock price. The coefficient of determination indicates that Company Size, NPM, and ROI only explain a small portion of the stock price variation, while the remainder is influenced by other factors outside the research model.